1975
DOI: 10.1159/000240776
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Steroids in Urine of the Male Newborn

Abstract: Four different methods of isolation and purification were utilized to study steroids in urine of male newborns which was collected during the first 5 days of life. These methods included celite column, ion exchange column and thin-layer chromatography, solvolysis and enzyme hydrolysis with β-glucuronidase and aryl sulfatase. Procedural losses were evaluated by using radioactive internal standards. Final quantitation of each steroid was achieved by comparison of its chromatographic and quantitative behavior wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…16-DHP was initially identified in the mono-sulfate conjugate fraction of neonatal feces by Gustafsson et al 3) Subsequently, this steroid has been identified in human placenta, 4) urine, [5][6][7][8] gall-bladder bile, 9) meconium 10) and amniotic fluid. 11) Previously we also identified 16-DHP in the serum of immature infants and we suggested that it is a form of the sulfate conjugate, 16-DHP sulfate (16DHPS).…”
mentioning
confidence: 99%
“…16-DHP was initially identified in the mono-sulfate conjugate fraction of neonatal feces by Gustafsson et al 3) Subsequently, this steroid has been identified in human placenta, 4) urine, [5][6][7][8] gall-bladder bile, 9) meconium 10) and amniotic fluid. 11) Previously we also identified 16-DHP in the serum of immature infants and we suggested that it is a form of the sulfate conjugate, 16-DHP sulfate (16DHPS).…”
mentioning
confidence: 99%